Kemampuan Berpikir Kritis Siswa Dalam Menyelesaikan Soal Himpunan Berbasis Kesenian Wayang Topeng Kabupaten Malang Ditinjau Dari Self Regulated Learning - Thoyyibah, Rifqoh; Anggraini, Erni; Marhayati, Marhayati (SJME (Supremum Journal of Mathematics Education), 2024)
Critical thinking skills are important for students to have because they can help solve problems more logically. Critical thinking skills are closely related to students' self-regulated learning. To hone critical thinking skills, you can do story problems on set material. The story questions presented in this research are based on the masked puppet art of Malang Regency. This research aims to describe the critical thinking abilities of students who have high, medium and low levels of self-regulated learning in solving set questions based on the wayang mask art of Malang Regency. The approach used is qualitative with a descriptive type. Data collection techniques include questionnaires, tests and interviews. This research was carried out by selecting 3 subjects representing 1 student each from the high, medium and low self-regulated learning categories. The selection of 3 subjects was carried out based on the percentage results obtained from the questionnaire scores which had been distributed to 22 students of Annuriyah Islamic Middle School, Malang City. The results of this study show that there are differences between students with high, medium and low levels of self-regulated learning. Students with high levels of self-regulated learning have excellent critical thinking skills, because students have excellent analytical sharpness and thoroughness. Students with moderate self-regulated learning have poor critical thinking skills, because students are less sharp in carrying out analysis, so this results in a lack of accuracy and results in inaccurate final results. Students with low self-regulated learning have very poor critical thinking skills, because they are still not very sharp in recognizing, so this results in inaccuracy and produces inaccurate final results.